Success Stories of Tanzanian Women Entrepreneurship Programs in Alleviating Poverty: Insights from WORTH Program - Mwajabu Mbaruku; Darlene K. Mutalemwa (Entrepreneurial Business and Economics Review)
This study attempts to provide evidence on the relevance and type of support given by women entrepreneurship support programs in alleviating poverty among Tanzanian women entrepreneurs. As such, it argues that WORTH is beneficial for women entrepreneurs.